Dexamethasone-Enhanced Microdialysis and Penetration Injury - Jaquins-Gerstl, Andrea; Michael, Adrian C. (Frontiers in Bioengineering and Biotechnology, 2020)
Microdialysis probes, electrochemical microsensors and neural prosthetics are often used for in vivo monitoring, but these are invasive devices that are implanted directly into brain tissue. Although the selectivity, sensitivity, and temporal resolution of these devices have been characterized in detail, less attention has been paid to the impact of the trauma they inflict on the tissue or the effect of any such trauma on the outcome of the measurements they are used to perform. Factors affecting brain tissue reaction to the implanted devices include: the mechanical trauma during insertion, the foreign body response, implantation method and physical properties of the device (size, shape, and surface characteristics). Modulation of the immune response is an important step toward making these devices with reliable long-term performance. Local release of anti-inflammatory agents such as dexamethasone (DEX) are often used to mitigate the foreign body response. In this article microdialysis is used to locally deliver DEX to the surrounding brain tissue. This article discusses the immune response resulting from microdialysis probe implantation. This work will also briefly review the principles of microdialysis and the applications of DEX with microdialysis in i) neuronal devices, ii) dopamine and fast scan cyclic voltammetry, iii) the attenuation of microglial cells and iv) spreading depolarizations. The difficulties and complexities in these applications are herein discussed.